Premature infants with patent ductus arteriosus: Postnatal growth according to type of management - Kunal Babla; Theodore Dassios; Kuberan Pushparajah; Ann Hickey; Anne Greenough (Pediatrics and Neonatology)
Background: Patent Ductus Arteriosus (PDA) is a common condition, affecting nearly half of infants born before 28 weeks' of gestation, and it has been associated with poor growth. It is not known if different treatment modalities are associated with more profound growth impairment. Our aim was to compare differences in weight gain at 36 weeks' corrected gestational age (CGA) in premature infants that received medical, surgical or conservative management for PDA. Methods: We retrospectively reviewed notes of 208 infants born under 30 weeks' gestation with a diagnosis of PDA. Gestational age (GA) at birth, birth weight z-score, CGA and weight z-score at 36 weeks' CGA were collected. In our cohort, surgical closure was performed in infants who remained symptomatic after medical or conservative management. Results: Ninety-four infants had medical, 56 surgical and 58 conservative management. Surgically managed infants had a lower median (IQR) GA [24.4 (24.0–26.1) weeks'] than medically [25.4 (24.6–26.5) weeks'] or conservatively managed [26.4 (25.4–28.1) weeks', p < 0.001] infants. There was no difference in birth weight z-scores across the groups. Surgically managed infants demonstrated a greater decrease in weight z-score [−2.24 (−2.89 to −1.53)] compared to medically [−1.79 (−2.45 to −1.35)] and conservatively [−1.57 (−1.99 to −1.28), p < 0.001] managed infants between birth and 36 weeks' CGA. After adjusting for GA at birth, definitive treatment modality was significantly related to change in weight z-score from birth to 36 weeks' CGA (adjusted p = 0.022). Conclusion: Premature infants with PDA who were managed surgically had a greater degree of faltering growth compared to those who were treated medically or conservatively.